National Minorities in Europe (Czech Journal of International Relations, 1994)
A work has appeared on our book market that will surely interest not only the wider readership, but also experts, including political scientists and specialists in international relations. It is not surprising, because the issue of minorities is a much more significant factor in (not only European) politics than it might have seemed until recently. Šatav's work entitled National Minorities in Europe can therefore be classified among a number of similar ones that have been published in Europe at the moment and which are the same reaction to the actualization of this problem of modern European history.The author is an ethnographer, which corresponds to the focus of the work mainly on the so-called "old", original or autochthonous ethnic populations of Europe. In the opening chapter, however, he tries to think more generally about the issue of minorities and confirms that he is aware that his point of view is somewhat different from, for example, the point of view of a political scientist. At the same time, he appropriately relativizes the name "national minority" itself. He uses it for a rather practical reason. It is a traditional term in our environment, generally used and in a certain way covering, which suits Shatav best in his view of this issue.